Pelatihan Desain Grafis Pembuatan Katalog Produk Menggunakan Aplikasi Canva Di Desa Seketi, Mojoagung, Jombang - Moch. Faizul Huda (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
The Industrial Revolution 4.0 era emphasizes the digital economy pattern, artificial intelligence, big data, and robotics known as the disruptive innovation phenomenon. The need for design in this era creates business opportunities through the development of graphic designs that can be realized through visual media, this potential is widely captured by design studios and bureaus. The problem that occurs in Seketi Village, Mojoagung District, Jombang Regency is the lack of knowledge about graphic design as a promotional medium for businesses such as making banners, posters, or other designs. Limited knowledge can hinder the marketing process of products that have been produced. The use of unique product designs on social media can attract consumers, so efforts are needed to improve graphic design skills. Training is often considered the most common activity because it will make partners more skilled and productive in developing expertise. It is hoped that through graphic design training in making product catalogs for the Asman group and youth organizations in Seketi Village, Mojoagung District, Jombang Regency, graphic design skills can be improved more quickly and effectively. This training can boost creativity and technology management to encourage the progress of MSME products that have been produced.